Challenges experienced by informal caregivers in cancer - Girgis, A.; Johnson, C.; Aoun, Samar; Currow, D. (Australian Cancer Society, 2006)
Evidence from the literature highlights the significant negative impact of care giving on the physical, mental and financial aspects of caregivers' lives. It also reinforces the importance of reducing the barriers to meeting the unmet needs of caregivers and that research priorities in intervention development need to focus on reducing the negative aspects of care giving. Increased assistance to caregivers needs to ensure that they have the knowledge, skills, income security, job protection and other supports to provide care, while maintaining their own health and well-being throughout the dying and grieving process. This is particularly important in light of the predicted shortfall in the number in caregivers and especially as caregivers are increasingly replacing skilled health workers in the delivery of unfamiliar, complex cancer care at home.